Surgical management of ossifying fibroma in a 9-year-old Hungarian Vizsla: a case report and review of the literature - Pop, Romelia; Tăbăran, Alexandru-Flaviu; Vasiu, Iosif; Milgram, Joshua; Ober, Ciprian Andrei (Frontiers in Veterinary Science, 2025)
Ossifying fibroma (OF) is a rare, benign fibro-osseous neoplasm that primarily originates from membranous bones. While most frequently documented in equines, OF has also been reported in other species, including dogs, though it remains uncommon. The condition poses significant diagnostic challenges due to its ambiguous presentation, often requiring differentiation from other benign and malignant intraosseous lesions. This case report describes an ossifying fibroma localized to the zygomatic bone in a 9-year-old Hungarian Vizsla. A zygomatic arch ostectomy was successfully performed, and long-term follow-up was excellent. This is only the second documented case of zygomatic localization of OF in a dog, highlighting the rarity of this presentation. The discussion emphasizes the importance of distinguishing OF from other proliferative fibro-osseous lesions, such as fibrous dysplasia (FD) and cemento-osseous dysplasia (COD), and considering the potential for malignancies, such as low-grade osteosarcoma (LG-OSA), to mimic these benign growths. This case contributes valuable insights to the limited veterinary literature on ossifying fibroma, particularly regarding its atypical presentations in canine patients.